PENGARUH SISTEM PRESENSI FINGER PRINTDAN MOTIVASI BELAJAR SISWA TERHADAP KEDISIPLINAN SISWA DI SMK LABOR BINAAN FKIP UNRI PEKANBARU - Izazi, Nabilah Imamah; Sumarno, Sumarno; Karatikowati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the effectof the finger print attendance system & student motivation on student discipline in the SMK LABOR FKIP UNRI Pekanbaru. The population were 639 students of SMK LABOR FKIP UNRI Pekanbaru. The sample taken randomly using the Slovin formula as a sample gauge with an error rate of 5%. Data were collected using a questionnaire about finger print attendance, student motivation & student discipline that was distributed to respondents. Data analysis uses multiple linear regression analysis. The results of the descriptive analysis of the study explained that the finger print attendancesystem was in the category because the finger print attendancesystem was 45.75% implemented in the medium category and student learning motivation was 55.06% in the moderate category. While the results of multiple regression analysis finger print attendance had a direct positive influenceon student discipline of 0.065. Learning motivationhas a direct positive effecton student discipline of 0.994.KeyWords:Finger Print Presence System, Learning Motivation, And Student Discipline